Front Cover Picture: Redox‐Neutral Arylations of Vinyl Cation Intermediates (Adv. Synth. Catal. 1/2017). Issue 1 (4th January 2017) - Kaiser, Daniel; Veiros, Luis F.; Maulide, Nuno
Abstract : The front cover image, provided by Giovanni Di Mauro, Daniel Kaiser and Nuno Maulide, illustrates the conversion of vinyl cations, as high‐energy intermediates, into systems prone to charge‐accelerated Claisen‐type [3, 3]‐sigmatropic rearrangements. Starting from simple precursors, vinyl cation formation enables a rapid increase of molecular complexity, affording α‐arylated carbonyl compounds that can be easily elaborated into drug‐like scaffolds. The setting to this cascade of reactions is provided by the famous (and beautiful) Karlskirche in Vienna (Foto: G. Kücükkaplan). Further details can be found in the full paper on page 64–77 (D. Kaiser, L. F. Veiros, N. Maulide, Adv. Synth. Catal .2017, 359, 64–77; DOI:10.1002/adsc.201600860 )